A needs assessment on addressing environmental health issues within reproductive health service provision: Considerations for continuing education and support - Williamson, Linzi; Sangster, Sarah; Bayly, Melanie; Gibson, Kirstian; Clark, Megan; Lawson, Karen (Revue canadienne de l'éducation médicale, 2017)
Background: This needs assessment was initially undertaken to explore the beliefs and knowledge of nurses and physicians about the impact of environmental toxicants on maternal and infant health, as well as to describe current practice and needs related to addressing environmental health issues (EHI). Methods: One hundred and thirty-five nurses (n = 99) and physicians (n = 36) working in Saskatchewan completed an online survey. Survey questions were designed to determine how physicians and nurses think about and incorporate environmental health issues into their practice and means of increasing their capacity to do so. Results: Although participants considered it important to address EHIs with patients, in actual practice they do so with only moderate frequency. Participants reported low levels of knowledge about EHIs’ impact on health, and low levels of confidence discussing them with patients. Participants requested additional information on EHIs, especially in the form of online resources. Conclusion: The results suggests that while nurses and physicians consider EHIs important to address with patients, more education, support, and resources would increase their capacity to do so effectively. Based on the findings, considerations and recommendations for continuing education in this area have been provided.